2014
DOI: 10.1002/fsn3.118
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and total phenolic compounds of Dezful sesame cake extracts obtained by classical and ultrasound‐assisted extraction methods

Abstract: Sesame cake is a by-product of sesame oil industry. In this study, the effect of extraction methods (maceration and sonication) and solvents (ethanol, methanol, ethanol/water (50:50), methanol/water (50:50), and water) on the antioxidant properties of sesame cake extracts are evaluated to determine the most suitable extraction method for optimal use of this product. Total phenolic content is measured according to the Folin–Ciocalteu method and antioxidant activities of each extract are evaluated with the 2,2-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 51 publications
5
30
0
1
Order By: Relevance
“…For the control sample, all the compounds and conditions mentioned were used without adding extracts. The following formula has been used to control the free radicals (Esmailzadeh Kenari et al, ). Synthetic antioxidant TBHQ was used as a positive control at 100 ppm.%0.333333emDPPH free radical scavenging=Sample absorbance-DPPH/DPPH absorbance…”
Section: Methodsmentioning
confidence: 99%
“…For the control sample, all the compounds and conditions mentioned were used without adding extracts. The following formula has been used to control the free radicals (Esmailzadeh Kenari et al, ). Synthetic antioxidant TBHQ was used as a positive control at 100 ppm.%0.333333emDPPH free radical scavenging=Sample absorbance-DPPH/DPPH absorbance…”
Section: Methodsmentioning
confidence: 99%
“…The solvent was completely evaporated in an oven at 40°C. Finally, the obtained extract was stored in a dark container in refrigerator (4°C) until use (Esmaeilzadeh Kenari et al 2014). EOs were extracted by hydrodistillation from the powdered PW by the Clevengertype apparatus, and the obtained oil was stored in a dark container in refrigerator (4°C) until use.…”
Section: Preparation Of Pwe and Pweomentioning
confidence: 99%
“…Similar previously published results such as the study by Esmaeilzadeh Kenari et al . () and Hasmida et al . () revealed that the supercritical CO 2 and ultrasound‐assisted extraction methods were more effective to extract phenolic compounds compared to solvent extraction method.…”
Section: Resultsmentioning
confidence: 93%
“…The solvents were completely evaporated in an oven at 40C. Finally, they were placed in a refrigerator (Chang et al 2002;Esmaeilzadeh Kenari et al 2014).…”
Section: Maceration Extractionmentioning
confidence: 99%